Հայկ Նահապետի ժամանակաշրջանի թվագրման փորձ - Հակոբյան, (Թարումյան) Ռուբեն (ՀՀ ԳԱԱ հրատ.)
В арменоведении распространено мнение, что родоначальники армян Айк, Арам, Ара Прекрасный и другие, а также противник Айка–Бел, о которых повествуется в Истории Армении Мовсеса Хоренаци, являются мифическими персонажами. Однако отдельными исследователями были предложены идентификации некоторых из этих персонажей с реальными историческими лицами, известными из клинописных источников. In the Armenian Studies it is widely believed that the ancestors of the Armenians Hayk, Aram, Ara the Beautiful, and others, as well as the adversary of Hayk–Bel, which is narrated in the History of Armenia by Movses Khorenatsi, are mythical characters. However, some researchers have proposed the identification of some of these characters with real historical persons known from cuneiform sources.
Keywords: Հայագիտություն; Պատմություն